Exam ref AZ-203 developing solutions for Microsoft Azure - Muñoz, Santiago Fernández (Microsoft : Pearson Education, 2020)
Prepare for Microsoft Exam AZ-203 --and help demonstrate your real-world mastery of Microsoft Azure solutions development. Designed for working Azure developers, this Exam Ref focuses on the critical thinking and decision-making acumen needed for success at the Microsoft Certified Solutions Associate level. Focus on the expertise measured by these objectives: " Develop Azure Infrastructure as a Service compute solutions " Develop Azure Platform as a Service compute solutions " Develop for Azure storage " Implement Azure security " Monitor, troubleshoot, and optimize solutions " Connect to and consume Azure and third-party services This Microsoft Exam Ref : " Organizes its coverage by exam objectives " Features strategic, what-if scenarios to challenge you " Assumes you want to show your ability to design and build diverse Microsoft Azure cloud solutions, and successfully participate in all phases of their development. About the Exam Exam AZ-203 focuses on knowledge needed to implement solutions using VMs and containers; implement batch jobs; create Azure App Service apps; implement Azure functions; develop solutions with storage tables, Cosmos DB, relational databases, or blobs; implement authentication, access control, and secure data solutions; support app and service scalability; integrate caching and content delivery; instrument solutions; develop App Service Logic Apps; integrate Azure Search; establish API gateways; and develop event- and message-based solutions. About Microsoft Certification Passing this exam fulfills your requirements for the Microsoft Certified: Azure Developer Associate credential, demonstrating your readiness to design, build, test, and maintain Microsoft Azure cloud solutions, and partner with other cloud professionals and clients to implement them. This exam is also a prerequisite for the Microsoft Certified: Azure DevOps Engineer Expert credential. See full details at: microsoft.com/learn